Robo4‐mediated pancreatic endothelial integrity decreases inflammation and islet destruction in autoimmune diabetes. Issue 2 (9th January 2020) - Troullinaki, Maria; Chen, Lan‐Sun; Witt, Anke; Pyrina, Iryna; Phieler, Julia; Kourtzelis, Ioannis; Chmelar, Jindrich; Sprott, David; Gercken, Bettina; Koutsilieris, Michael; Chavakis, Triantafyllos; Chatzigeorgiou, Antonios
Abstract: In Type 1 Diabetes Mellitus (T1DM), leukocyte infiltration of the pancreatic islets and the resulting immune‐mediated destruction of beta cells precede hyperglycemia and clinical disease symptoms. In this context, the role of the pancreatic endothelium as a barrier for autoimmunity‐ and inflammation‐related destruction of the islets is not well studied. Here, we identified Robo4, expressed on endothelial cells, as a regulator of pancreatic vascular endothelial permeability during autoimmune diabetes. Circulating levels of Robo4 were upregulated in mice subjected to the Multiple Low‐Dose Streptozotocin (MLDS) model of diabetes. Upon MLDS induction, Robo4‐deficiency resulted in increased pancreatic vascular permeability, leukocyte infiltration to the islets and islet apoptosis, associated with reduced insulin levels and faster diabetes development. On the contrary, in vivo administration of Slit2 in mice modestly delayed the emergence of hyperglycaemia and ameliorated islet inflammation in MLDS‐induced diabetes. Thus, Robo4‐mediated endothelial barrier integrity reduces insulitis and islet destruction in autoimmune diabetes. Our findings highlight the importance of the endothelium as gatekeeper of pancreatic inflammation during T1DM development and may pave the way for novel Robo4‐related therapeutic approaches for autoimmune diabetes.